2021
DOI: 10.1177/00099228211020177
|View full text |Cite
|
Sign up to set email alerts
|

Serum Alanine Transaminase Is an Inadequate Nonalcoholic Fatty Liver Screening Test in Adolescents: Results From the National Health and Nutrition Examination Survey 2017-2018

Abstract: Nonalcoholic fatty liver disease (NAFLD) is common in overweight adolescents, and screening with serum alanine transaminase (ALT) levels is recommended by the American Academy of Pediatrics. We sought to determine if ALT is an accurate adolescent screening measure for NAFLD in a nationally representative sample of overweight adolescents. Diagnosis of NAFLD was determined using vibration-controlled transient elastography. Analyses were performed to calculate the sensitivity, specificity, positive predictive val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, some researchers have presented contrasting results. For instance, Abrams et al proposed that serum ALT levels were not an adequate screening tool to detect NAFLD [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some researchers have presented contrasting results. For instance, Abrams et al proposed that serum ALT levels were not an adequate screening tool to detect NAFLD [30].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Abrams et al . proposed that serum ALT levels were not an adequate screening tool to detect NAFLD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, the American Academy of Pediatrics (AAP) issued guidelines that recommended using serum alanine transaminase (ALT), aware of its limitations, to screen for NAFL and NAFLD 9 . However, recent studies, have demonstrated the poor diagnostic sensitivity of serum ALT for identifying adolescents with NAFL or NAFLD 10,11 . Therefore, there are limited clinically useful parameters by which to determine who should be screened for NAFL and NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, recent studies, have demonstrated the poor diagnostic sensitivity of serum ALT for identifying adolescents with NAFL or NAFLD. 10,11 Therefore, there are limited clinically useful parameters by which to determine who should be screened for NAFL and NAFLD.…”
mentioning
confidence: 99%